1996
DOI: 10.1002/pssa.2211530113
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal investigation of the switching phenomena in p-type TlInSe2 single crystals

Abstract: Large TlInSe2 single crystals are grown by the Bridgman‐Stockbarger method, starting from stoichiometric melts. Current–voltage (I–V) characterstics of symmetric In/p‐TlInSe2/In structures exhibit two distinct regions: an ohmic region at low current densities and a non‐linear region (S‐shaped) having negative differential resistance (NDR) at moderate and higher current densities. An electrothermal model is used for the explanation of this non‐linear behaviour. The non‐linear behaviour of the I–V curves is stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…electrothermal model [22] , the ambient temperature greatly influences both the form of the i-v curves and the threshold voltage V th , that is, there is a weaker appearance of the NDR region of the i-v characteristics at higher temperature. There exist some fluctuation in the value of V th , when the first three or four switching cycles were measured.…”
Section: Resultsmentioning
confidence: 99%
“…electrothermal model [22] , the ambient temperature greatly influences both the form of the i-v curves and the threshold voltage V th , that is, there is a weaker appearance of the NDR region of the i-v characteristics at higher temperature. There exist some fluctuation in the value of V th , when the first three or four switching cycles were measured.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the ternary (i.e., consisting of three different elements) semiconductor TLMX 2 [8], with M=Ga (Gallium) and In (Indium), and X=Se (Selenium), S (Sulfur) and Te (Tellurium), as well as the TLInX 2 -TLSmX 2 alloys [9], with X=S, Se, or Te, exhibit nonlinear effects on their current-voltage (I-V) characteristics (including a region of negative differential resistance), switching, and memory effects [6][7][8]. The electrical conductivity of several chain-type crystals exhibits time oscillations and intermittency [6][7][8]10]. These nonlinear effects, such as negative differential resistance, are the result of an electro-thermal mechanism [6,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity of several chain-type crystals exhibits time oscillations and intermittency [6][7][8]10]. These nonlinear effects, such as negative differential resistance, are the result of an electro-thermal mechanism [6,7,10]. The switching occurs because of deviations in the uniform distribution of the imperfection.…”
Section: Introductionmentioning
confidence: 99%
“…TlInSe 2 exhibits very interesting physical properties in the temperature range 140-430 K, for example, different nonlinear effects in the electrical behavior of crystals, such as SÀtype currentvoltage characteristics with voltage oscillations in the negative resistance region, switching and memory effects. [8][9][10][11] Recently it has been found that TlInSe 2 is characterized by giant values of the Seebeck coefficient at the temperature region of 320-430 K. [12][13][14] The Seebeck coefficient (thermopower) is a measure of the value of the thermoelectric voltage induced by the response to a temperature difference across the material. The giant value of Seebeck coefficient of TlInSe 2 is % 105-107 μV K À1 in the specified temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…TlInSe 2 exhibits very interesting physical properties in the temperature range 140–430 K, for example, different nonlinear effects in the electrical behavior of crystals, such as S−type current – voltage characteristics with voltage oscillations in the negative resistance region, switching and memory effects . Recently it has been found that TlInSe 2 is characterized by giant values of the Seebeck coefficient at the temperature region of 320–430 K …”
Section: Introductionmentioning
confidence: 99%